Electromagnetic shielding polyurethane porous fiber membrane with sandwich structure and preparation method thereof
By constructing a sandwich-structured electromagnetic shielding polyurethane porous fiber membrane on a polymer fiber membrane, and utilizing the combination of a conductive network of metal nanoparticles and a dielectric electromagnetic synergistic layer, the problem of insufficient impedance matching and attenuation capability in the prior art is solved, achieving highly efficient electromagnetic interference shielding performance and structural stability.
Patent Information
- Application Number
- CN202511422071.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2026-01-09
AI Technical Summary
Existing electromagnetic shielding materials have contradictions in impedance matching and attenuation capabilities, and lack structural stability and multiple reflection/scattering mechanisms, resulting in poor electromagnetic interference shielding performance.
An electromagnetic shielding polyurethane porous fiber membrane with a sandwich structure is formed by creating a dielectric electromagnetic synergistic layer on the surface of the polymer fiber membrane, consisting of a conductive network of metal nanoparticles, a polyaniline nanoshell, and a layered double hydroxyl oxide layer, combined with hot pressing to form a stable multilayer structure.
It achieves excellent impedance matching, strong absorption and attenuation capabilities, and high structural stability, significantly reducing secondary reflection pollution, improving the efficiency of multiple reflections and scattering of electromagnetic waves, and extending the propagation path.
Smart Images

Figure CN121290894A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic shielding materials technology, and particularly relates to a sandwich-structured electromagnetic shielding polyurethane porous fiber membrane and its preparation method. Background Technology
[0002] Electromagnetic waves, as a key medium for information transmission, can not only interfere with electronic devices but also potentially increase health risks such as cancer, migraines, and damage to the reproductive system. Polymer-based electromagnetic wave shielding materials are widely used due to their advantages such as structural stability, light weight, corrosion resistance, and high elasticity. However, achieving high performance requires a coordinated solution to the contradiction between impedance matching and attenuation capability.
[0003] In existing technologies, relying solely on conductive materials with high conductivity can easily lead to strong reflections and secondary pollution. While using only magnetic loss materials can optimize impedance matching, their large skin depth and low inherent conductivity at high frequencies result in insufficient shielding effectiveness. Therefore, researchers often blend conductive and magnetic loss fillers into polymer matrices or construct asymmetric multilayer structures, such as magnetic loss layers / conductive layers, in an attempt to synergistically resolve the contradiction between impedance matching and attenuation. However, blending can easily lead to a sudden drop in local impedance due to conductive fillers, disrupting the overall matching, and the magnetic loss path is discontinuous due to the separation of conductive particles, resulting in poor electromagnetic interference shielding performance. Currently, asymmetric multilayer structures can precisely control impedance matching and attenuation capabilities, improving electromagnetic shielding effectiveness. However, they generally suffer from stability problems such as weak interlayer bonding and easy peeling and breakage due to the brittle conductive layer. Furthermore, their dense, non-porous structure severely limits the scattering, multiple reflections, and deep absorption of electromagnetic waves internally, weakening the shielding effectiveness, especially the absorption-dominated one.
[0004] Therefore, there is an urgent need to develop a new type of electromagnetic shielding material that combines excellent impedance matching, strong absorption and attenuation capabilities, high structural stability, and efficient multiple reflection / scattering mechanisms. Summary of the Invention
[0005] To overcome the shortcomings of the prior art, the present invention aims to provide a sandwich-structured electromagnetic shielding polyurethane porous fiber membrane, which possesses excellent impedance matching, strong absorption attenuation capability, high structural stability, and efficient multiple reflection / scattering mechanism; another objective of the present invention is to provide a method for preparing the sandwich-structured electromagnetic shielding polyurethane porous fiber membrane.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A sandwich-structured electromagnetic shielding polyurethane porous fiber membrane includes an intermediate electromagnetic synergistic layer and surface conductive layers pressed onto both sides of the intermediate electromagnetic synergistic layer; the intermediate electromagnetic synergistic layer is a double-shell structure in which a polyaniline nanoshell layer and a layered double hydroxyl oxide layer are sequentially formed on the surface of the polymer fiber membrane; the surface conductive layers are a conductive network formed by growing metal nanoparticles on the surface of the polymer fiber membrane; the polymer fiber membrane is a polyurethane fiber membrane.
[0008] Furthermore, the thickness of the polyaniline nanoshell is 40~60 nm; the thickness of the sandwich structure electromagnetic shielding polyurethane porous fiber membrane is 200~400 μm.
[0009] Furthermore, the thickness ratio of the two surface conductive layers is 1:(0.8~1.2), and the thickness of the intermediate electromagnetic synergistic layer is 1.5~2.5 times that of the surface conductive layer.
[0010] Furthermore, the metal nanoparticles are gold, silver, copper, aluminum or their alloy nanospheres, with a particle size of 20-50 nm, preferably 35-45 nm.
[0011] Furthermore, the metal complex coverage of the surface conductive layer is >90%, and the conductivity is >850 S / m.
[0012] This invention provides a method for preparing the above-mentioned sandwich-structured electromagnetic shielding polyurethane porous fiber membrane, comprising the following steps:
[0013] S1. Preparation of the surface conductive layer: The polyurethane fiber membrane is immersed in a reaction solution in which metal ions are reduced by in-situ solution reduction method. The reaction is controlled so that metal nanoparticles with a particle size of 20~50 nm grow in situ on the fiber surface to form a conductive network.
[0014] S2. Preparation of intermediate electromagnetic synergistic layer: A polyaniline nanoshell with a thickness of 40-60 nm is formed on the surface of the polyurethane fiber membrane by immersing it in a solution generated by the polymerization reaction of polyurethane fiber membrane and polyaniline; the obtained polyaniline nanoshell is then immersed in a solution generated by the reaction of layered dihydroxyoxide layer to form a layered dihydroxyoxide layer on the surface of the polyaniline nanoshell, thus obtaining an intermediate electromagnetic synergistic layer with a polyaniline nanoshell and a layered dihydroxyoxide layer;
[0015] S3. Structural Assembly: Two surface conductive layers are placed on both sides of the intermediate electromagnetic synergistic layer to form a sandwich stacked structure; then hot pressing is performed to make the three layers partially melt or viscous flow at the interface to achieve a firm bond, maintaining a porosity of 60-80%, and obtaining a sandwich structure electromagnetic shielding polyurethane porous fiber membrane.
[0016] Furthermore, the polyurethane fiber membrane is prepared by electrospinning. The spinning solution is formed by dissolving 18-21 wt% polyurethane and 0.08-0.12 wt% sodium dodecyl sulfate in a DMF / THF mixed solvent with a DMF / THF volume ratio of 3.5:6.5 to 6.5:3.5, to prepare a polyurethane fiber membrane with a diameter of 450-550 nm and a porosity of >85%.
[0017] Further, the reaction solution for reducing metal ions in step S1 includes the following components: a mixed solution of 0.8~1.2 mmol MAgNO3, 1.0~1.5 wt% trisodium citrate, and 0.1~0.3 wt% PVP~K30; the reaction conditions are: shaking at 60±2℃ for 20~40 min.
[0018] Further, the solution generated by the polyaniline polymerization reaction in step S2 contains: 0.1~0.3 M aniline monomer, 0.08~0.24 M ammonium persulfate, 0.5~1.0 M camphor sulfonic acid and 0.01~0.05 wt% potassium perfluorooctyl sulfonate; the reaction conditions are: reacting at a low temperature of 4~6℃ for 5~8 min, then raising the temperature to 24~26℃ and reacting for 40~50 min.
[0019] Further, the solution generated by the layered dihydroxyoxide layer reaction in step S2 comprises: a mixed alkaline solution of 0.05~0.15 M divalent metal salt, 0.025~0.075 M trivalent metal salt, 0.1~0.3 M urea, and 0.05 M boric acid-borax buffer; wherein the divalent metal salt is Ni. 2+ or Fe 2+ or Co 2+ The trivalent metal salt is Fe. 3+ Or Al 3+ The reaction conditions were: hydrothermal reaction at 78±2℃ for 40~60 min.
[0020] Preferably, the layered dihydroxy oxide of the layered dihydroxy oxide layer is any one of NiFe-LDH, CoFe-LDH, NiAl-LDH, NiCoFe-LDH, and NiCoAl-LDH.
[0021] Preferably, the hot pressing treatment described in S3 is performed under the following conditions: temperature of 60-80°C, pressure of 0.5-2.0 MPa, and time of 30-120 s.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The sandwich structure electromagnetic shielding polyurethane porous fiber membrane of the present invention achieves electromagnetic wave progressive dissipation by growing metal nanoparticles on the surface of the polymer fiber membrane to form two conductive layers and a middle electromagnetic synergistic layer of a double shell structure of polyaniline nanoshell and layered dihydroxy oxide sequentially generated on the surface of the polymer fiber membrane. The conductive layer on one side reflects the first incident wave by utilizing the skin effect and eddy current loss; the polyaniline nanoshell of the middle electromagnetic synergistic layer induces interface polarization, and the layered dihydroxy oxide layer generates hysteresis loss and natural resonance, which synergistically optimizes impedance matching; the residual wave of the second reflection of the bottom layer of the conductive layer on the other side continues to attenuate to the middle electromagnetic synergistic layer, forming a closed-loop mechanism of "reflection-absorption-rereflection", which significantly reduces secondary reflection pollution.
[0024] (2) The sandwich structure electromagnetic shielding polyurethane porous fiber membrane structure enhances multiple scattering and impedance gradient, forcing electromagnetic waves to undergo multiple reflections and scatterings between the pore walls, thus extending the propagation path; at the same time, the composition gradient distribution of the layered double hydroxyl oxide layer / polyaniline nanoshell / nano metal spheres on the fiber surface is constructed to form a continuous impedance gradient layer, reducing interface reflection and improving low-frequency absorption efficiency.
[0025] (3) By hot pressing, the surface of the polyurethane fiber membrane is partially melted and interlocked while maintaining the stability of the pore structure, overcoming the problem of easy peeling between layers and pore collapse caused by traditional asymmetric materials, thus achieving long-term stability. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the sandwich structure electromagnetic shielding polyurethane porous fiber membrane structure in Example 1.
[0027] In the figure, 1 represents the intermediate electromagnetic synergistic layer; 2 represents the surface conductive layer.
[0028] Figure 2 This is a SEM image of the polyurethane fiber membrane in Example 1.
[0029] Figure 3 This is a SEM image of the sandwich-structured electromagnetic shielding polyurethane porous fiber membrane in Example 1.
[0030] Figure 4 The electromagnetic shielding effectiveness curve of the sandwich structure electromagnetic shielding polyurethane porous fiber membrane in Example 2 is shown.
[0031] Figure 5 The electromagnetic shielding effectiveness curve of the sandwich structure electromagnetic shielding polyurethane porous fiber membrane in Example 3 is shown.
[0032] Figure 6 The effect of nano-silver type on the electromagnetic shielding effectiveness of materials.
[0033] Figure 7The effect of silver nanoparticle size on the electromagnetic shielding effectiveness of the material.
[0034] Figure 8 The effect of aniline dosage on the electromagnetic shielding effectiveness of the material.
[0035] Figure 9 The effect of hot pressing on the interlaminar peel strength of composite materials. Detailed Implementation
[0036] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0037] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate so that the embodiments of the invention described herein can be implemented in orders other than those illustrated or described herein. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover a non-exclusive inclusion; for example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to such processes, methods, products, or apparatus.
[0038] The following specific embodiments further illustrate the asymmetric electromagnetic shielding polyurethane fiber membrane and its preparation method according to the present invention:
[0039] Example 1
[0040] like Figure 1 This embodiment provides a sandwich structure electromagnetic shielding polyurethane porous fiber membrane, including an intermediate electromagnetic synergistic layer 1 and surface conductive layers 2 hot-pressed on both sides of the intermediate electromagnetic synergistic layer; the intermediate electromagnetic synergistic layer 1 is a double shell structure in which a polyaniline nanoshell and a layered double hydroxyl oxide layer are sequentially generated on the surface of the polymer fiber membrane; the surface conductive layer 2 is a conductive network formed by growing metal nanoparticles on the surface of the polymer fiber membrane; the polymer fiber membrane is a polyurethane fiber membrane.
[0041] This embodiment provides a method for preparing the sandwich-structured electromagnetic shielding polyurethane porous fiber membrane, including the following steps.
[0042] S1. Preparation of the surface conductive layer: The polyurethane fiber membrane is immersed in a reaction solution in which metal ions are reduced by in-situ solution reduction method. The reaction is controlled so that metal nanoparticles with a particle size of 20~50 nm grow in situ on the fiber surface to form a conductive network.
[0043] S2. Preparation of intermediate electromagnetic synergistic layer: Polyurethane fiber membrane and polyaniline are polymerized in a solution to form a polyaniline nanoshell on the surface of the polyurethane fiber membrane; the obtained polyaniline nanoshell is immersed in a solution generated by the reaction of layered dihydroxyoxides to form a layered dihydroxyoxide layer on the surface of the polyaniline nanoshell, thus obtaining an intermediate electromagnetic synergistic layer with a polyaniline nanoshell and a layered dihydroxyoxide layer.
[0044] S3. Structural Assembly: Two surface conductive layers are placed on both sides of the intermediate electromagnetic synergistic layer to form a sandwich stacked structure; then hot pressing is performed to make the three layers partially melt or viscous flow at the interface to achieve a firm bond, resulting in a sandwich structure electromagnetic shielding polyurethane porous fiber membrane.
[0045] The specific method is as follows:
[0046] (1) A DMF / THF (6:4) spinning solution of 21 wt% PU and 0.11 wt% sodium dodecyl sulfate was prepared. Electrospinning was carried out at 19 kV voltage, 1.3 mL / h flow rate and 16 cm receiving distance to obtain a PU fiber membrane with a diameter of 540±35 nm and a porosity of 89%. Subsequently, the membrane was immersed in a mixed solution containing 1.1 mM AgNO3, 1.4 wt% trisodium citrate and 0.25 wt% PVP-K30 and shaken at 61℃ for 25 min to generate nanospheres of silver with a diameter of 45±3 nm, a coverage of 95% and a conductivity of 920 S / m.
[0047] (2) The PU fiber membrane was immersed in a solution containing 0.2 M aniline, 0.18 M APS, 0.8 M HCl, and 0.03 wt% potassium perfluorooctyl sulfonate. After reacting at 5°C for 7 min, the temperature was increased to 25°C and reacted for 45 min to form a PANI nanoshell with a thickness of 53±6 nm. After cleaning with deionized water, it was immersed in a solution containing 0.10 M Ni(NO3)2, 0.033 M Fe(NO3)3, 0.2 M urea, and 0.05 M borax buffer (pH=9.2). After reacting at 65°C for 50 min, a NiFe-LDH nanosheet array was vertically grown on the PANI surface.
[0048] (3) Take two layers of PU@Ag membrane (each with a thickness of 150 μm) and sandwich the middle layer of PU@PANI / NiFe-LDH membrane (thickness of 350 μm). Hot press at 70℃ and 1.0 MPa for 60 s to form a fiber melt interlocking structure between the layers. The thickness of the sandwich structure polyurethane porous fiber membrane is about 450 μm and the porosity is 78%.
[0049] See Figure 2 The image shows a SEM image of the PU fiber membrane prepared in Example 1 of the invention. As can be seen from the image, the polyurethane fiber membrane exhibits a relatively smooth and uniform fiber surface, with a relatively consistent fiber diameter distribution and a relatively loose arrangement between the fibers. (Refer to...) Figure 3 This is a SEM image of the sandwich-structured polyurethane porous fiber membrane obtained after hot pressing, showing its three-layer structure; combined with Figure 1 Its working principle is as follows: the conductive layer on one side reflects the first incident wave using the skin effect and eddy current loss; the polyaniline nanoshell with electromagnetic synergy in the middle induces interface polarization, and the layered double hydroxyl oxide layer generates hysteresis loss and natural resonance, which synergistically optimizes impedance matching; the residual wave reflected by the bottom layer of the conductive layer on the other side continues to attenuate to the middle electromagnetic synergy layer, forming a closed-loop mechanism of "reflection-absorption-re-reflection", which significantly reduces secondary reflection pollution.
[0050] Example 2
[0051] like Figure 1 This embodiment provides a sandwich-structured electromagnetic shielding polyurethane porous fiber membrane, which is basically the same as the preparation method in Example 1, except that the solution parameters and conditions are different. The specific preparation method is as follows:
[0052] (1) A DMF / THF (4:6) spinning solution of 20 wt% PU and 0.09 wt% sodium dodecyl sulfate was prepared. Electrospinning was carried out at 17 kV voltage, 1.1 mL / h flow rate and 14 cm receiving distance to obtain a PU fiber membrane with a diameter of 490±40 nm and a porosity of 86%. Subsequently, the membrane was immersed in a mixed solution containing 0.9 mM AgNO3, 1.1 wt% trisodium citrate and 0.15 wt% PVP-K30 and shaken at 59℃ for 35 min to generate nanospheres of silver with a diameter of 38±5 nm, a coverage of 91% and an electrical conductivity of 870 S / m.
[0053] (2) The PU fiber membrane was immersed in a solution containing 0.15 M aniline, 0.10 M APS, 0.6 M camphor sulfonic acid, and 0.02 wt% potassium perfluorooctyl sulfonate. After reacting at 4℃ for 8 min, the temperature was raised to 24℃ and reacted for 48 min to form a PANI nanoshell with a thickness of 48±7 nm. After cleaning with deionized water, it was immersed in a solution containing 0.07 M Co(NO3)2, 0.028 M Fe(NO3)3, 0.15 M urea, and 0.05 M borax buffer (pH=8.8). After reacting at 70℃ for 45 min, a CoFe-LDH nanosheet array was vertically grown on the PANI surface.
[0054] (3) Take two layers of PU@Ag membrane (each 90 μm thick) and sandwich the middle layer of PU@PANI / CoFe-LDH membrane (180 μm thick). Hot press at 65℃ and 0.8 MPa for 90 s to form a fiber melt interlocking structure between the layers. The thickness of the sandwich structure polyurethane porous fiber membrane is about 240 μm and the porosity is 75%.
[0055] See Figure 4 To assess the electromagnetic shielding effectiveness of the sandwich-structured electromagnetic shielding polyurethane porous fiber membrane prepared in Example 2 of the invention, the testing method was based on the standard GB / T35679-2017, "Methods for Measuring Electromagnetic Parameters of Waveguide Devices Used in the Microwave Band of Solid Materials". Figure 4 As can be seen from the data, the average SE of the sandwich-structured electromagnetic shielding polyurethane porous fiber membrane in the X-band is approximately 67.8 dB.
[0056] Example 3
[0057] like Figure 1 This embodiment provides a sandwich-structured electromagnetic shielding polyurethane porous fiber membrane, which is basically the same as the preparation method in Example 1, except that the solution parameters and conditions are different. The specific preparation method is as follows:
[0058] 1) A DMF / THF (6:4) spinning solution of 21 wt% PU and 0.11 wt% sodium dodecyl sulfate was prepared. Electrospinning was performed at 19 kV, 1.3 mL / h flow rate, and 16 cm receiving distance to obtain a PU fiber membrane with a diameter of 540±35 nm and a porosity of 89%. Subsequently, the membrane was immersed in a mixed solution containing 1.1 mM AgNO3, 1.4 wt% trisodium citrate, and 0.25 wt% PVP-K30, and shaken at 61℃ for 25 min to generate nanospheres of silver with a diameter of 45±3 nm, a coverage of 95%, and a conductivity of 920 S / m.
[0059] 2) The PU fiber membrane was immersed in a solution containing 0.25 M aniline, 0.20 M APS, 0.9 M HCl, and 0.04 wt% potassium perfluorooctyl sulfonate. After reacting at 6°C for 6 min, the temperature was increased to 26°C and reacted for 42 min to form a PANI nanoshell with a thickness of 57±5 nm. After cleaning with deionized water, it was immersed in a solution containing 0.12 M Ni(NO3)2, 0.05 M Co(NO3)2, 0.035 M Al(NO3)3, 0.25 M urea, and 0.05 M borax buffer (pH=10). After reacting at 75°C for 40 min, a NiCoAl-LDH nanosheet array was vertically grown on the PANI surface.
[0060] 3) Take two layers of PU@Ag membrane (each 120 μm thick) and sandwich the middle layer of PU@PANI / NiCoAl-LDH membrane (250 μm thick). Hot press at 75℃ and 1.8 MPa for 40 s to form a fiber melt interlocking structure between the layers. The thickness of the sandwich structure polyurethane porous fiber membrane is about 370 μm and the porosity is 81%.
[0061] See Figure 5 To improve the electromagnetic shielding effectiveness of the sandwich-structured electromagnetic shielding polyurethane porous fiber membrane prepared in Example 3 of the invention, from... Figure 5 As can be seen from the data, the average SE of the sandwich-structured electromagnetic shielding polyurethane porous fiber membrane in the X-band is approximately 82.3 dB.
[0062] Test Example 1
[0063] 1. Testing Method
[0064] The sandwich-structure electromagnetic shielding polyurethane porous fiber membrane prepared in Example 1, the PU fiber membrane prepared in Example 1 without subsequent intermediate electromagnetic synergistic layer and without growth of metal nanoparticle functional layer, and Ag nanowires prepared on the PU fiber membrane prepared in Example 1 were used as comparative experiments to test the average SE in the X-band.
[0065] 2. Test Results
[0066] Test results are as follows Figure 6 As shown, by Figure 6 It is known that using specific Ag nanoparticles can significantly improve the electromagnetic shielding effect.
[0067] Test Example 2
[0068] 1. Testing Method
[0069] Based on Example 3, the oscillation time in step 1) was changed so that the particle size of Ag nanoparticles prepared sequentially was 20 nm, 30 nm, 40 nm and 50 nm. The subsequent steps remained unchanged, and the average SE in the X-band was tested.
[0070] 2. Test Results
[0071] Test results are as follows Figure 7 As shown, by Figure 7 It can be seen that the electromagnetic shielding effect varies when using Ag nanoparticles with different particle sizes. Among them, Ag nanoparticles with a particle size of 30~50 nm have a better electromagnetic shielding effect, and Ag nanoparticles with a particle size of 40 nm have the best electromagnetic shielding effect.
[0072] Test Example 3
[0073] 1. Testing Method
[0074] Based on Example 3, the amount of aniline was changed to 0.1 M, 0.2 M and 0.3 M respectively, so that the thickness of the polyaniline nanoshell was 45±3 nm, 54±5 nm and 60±2 nm respectively. The subsequent steps remained unchanged, and the average SE was measured in the X-band.
[0075] 2. Test Results
[0076] Test results are as follows Figure 8 As shown, by Figure 8 It can be seen that different amounts of aniline result in different polyaniline nanoshells, leading to different electromagnetic shielding effects. Among them, 0.3 M of aniline has a better electromagnetic shielding effect.
[0077] Test Example 4
[0078] 1. Testing Method
[0079] The sandwich-structured electromagnetic shielding polyurethane porous fiber membrane prepared in Example 3 was pressed under normal temperature conditions, and the peel strength was tested. The test method was in accordance with GB / T 2792-2014 "Test method for 180° peel strength of pressure-sensitive adhesive tape".
[0080] 2. Test Results
[0081] Test results are as follows Figure 9 As shown, by Figure 9 It can be seen that the peel strength after hot pressing is 4.4, and without hot pressing, the layers cannot be effectively bonded and fixed.
[0082] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. A sandwich-structured electromagnetic shielding polyurethane porous fiber membrane, characterized in that, It includes an intermediate electromagnetic synergistic layer and surface conductive layers hot-pressed onto both sides of the intermediate electromagnetic synergistic layer; the intermediate electromagnetic synergistic layer is a double-shell structure in which a polyaniline nanoshell layer and a layered double hydroxyl oxide layer are sequentially formed on the surface of the polymer fiber membrane; the surface conductive layer is a conductive network formed by growing metal nanoparticles on the surface of the polymer fiber membrane; the polymer fiber membrane is a polyurethane fiber membrane.
2. The sandwich-structure electromagnetic shielding polyurethane porous fiber membrane according to claim 1, characterized in that, The thickness of the polyaniline nanoshell is 40~60 nm; the thickness of the sandwich structure electromagnetic shielding polyurethane porous fiber membrane is 200~400 μm.
3. The sandwich-structure electromagnetic shielding polyurethane porous fiber membrane according to claim 1, characterized in that, The thickness ratio of the two surface conductive layers is 1:(0.8~1.2), and the thickness of the intermediate electromagnetic synergistic layer is 1.5~2.5 times that of the surface conductive layers.
4. The sandwich-structure electromagnetic shielding polyurethane porous fiber membrane according to claim 1, characterized in that, The metal nanoparticles are gold, silver, copper, aluminum or their alloy nanospheres, with a particle size of 20-50 nm, preferably 35-45 nm.
5. The sandwich-structure electromagnetic shielding polyurethane porous fiber membrane according to claim 1, characterized in that, The surface conductive layer has a metal complex coverage of >90% and an electrical conductivity of >850 S / m.
6. A method for preparing the sandwich-structured electromagnetic shielding polyurethane porous fiber membrane according to any one of claims 1 to 5, characterized in that, Includes the following steps S1. Preparation of the surface conductive layer: The polyurethane fiber membrane is immersed in the reaction solution in which metal ions are reduced by the in-situ solution reduction method. The reaction is controlled so that metal nanoparticles with a particle size of 20~50 nm grow in situ on the fiber surface to form a conductive network. S2. Preparation of intermediate electromagnetic synergistic layer: A polyaniline nanoshell with a thickness of 40-60 nm is formed on the surface of the polyurethane fiber membrane by immersing it in a solution generated by the polymerization reaction of polyurethane fiber membrane and polyaniline; the obtained polyaniline nanoshell is then immersed in a solution generated by the reaction of layered dihydroxyoxides to form a layered dihydroxyoxide layer on the surface of the polyaniline nanoshell, thus obtaining an intermediate electromagnetic synergistic layer with a polyaniline nanoshell and a layered dihydroxyoxide layer; S3. Structural Assembly: Two surface conductive layers are placed on both sides of the intermediate electromagnetic synergistic layer to form a sandwich stacked structure; then hot pressing is performed to make the three layers partially melt or viscous flow at the interface to achieve a firm bond, maintaining a porosity of 60-80%, and obtaining a sandwich structure electromagnetic shielding polyurethane porous fiber membrane.
7. The method according to claim 6, characterized in that, The polyurethane fiber membrane was prepared by electrospinning. The spinning solution was formed by dissolving 18-21 wt% polyurethane and 0.08-0.12 wt% sodium dodecyl sulfate in a DMF / THF mixed solvent with a DMF / THF volume ratio of 3.5:6.5 to 6.5:3.
5. The polyurethane fiber membrane with a diameter of 450-550 nm and a porosity of >85% was prepared.
8. The method according to claim 6, characterized in that, The reaction solution for reducing metal ions in step S1 comprises the following components: a mixed solution of 0.8~1.2 mM AgNO3, 1.0~1.5 wt% trisodium citrate, and 0.1~0.3 wt% PVP~K30; The reaction conditions are: 60±2℃, shaking for 20~40 min.
9. The method according to claim 6, characterized in that, The solution generated by the polyaniline polymerization reaction in step S2 contains: 0.1~0.3 M aniline monomer, 0.08~0.24 M ammonium persulfate, 0.5~1.0 M camphor sulfonic acid and 0.01~0.05 wt% potassium perfluorooctyl sulfonate; the reaction conditions are: reacting at a low temperature of 4~6℃ for 5~8 min, then raising the temperature to 24~26℃ and reacting for 40~50 min.
10. The method according to claim 6, characterized in that, The solution generated by the layered dihydroxyoxide reaction in step S2 comprises: a mixed alkaline solution of 0.05~0.15 M divalent metal salt, 0.025~0.075 M trivalent metal salt, 0.1~0.3 M urea, and 0.05 M boric acid-borax buffer; wherein the divalent metal salt is Ni. 2+ or Fe 2+ or Co 2+ The trivalent metal salt is Fe. 3+ Or Al 3+ The reaction conditions were: hydrothermal reaction at 78±2℃ for 40~60 min.